Technology utilization model to promote health literacy in the learning resource center for the elderly - Chotjirawatthana, Sriprai; Tantrarungroj, Pornsook; Suwanmonkma, Siripaarn (Kasetsart Journal of Social Sciences, 2021)
This research aims to develop the technology utilization model to promote health literacy in the learning resource center for the elderly. The research was divided into two phases. The first phase began with studying the needs for a technology utilization model to promote health literacy. This involved six experts and 434 elderly people in Bangkok, Thailand, and its vicinities. A technology utilization model was developed to promote health literacy, which was assessed by seven experts. The second phase involved studying the results of using the technology utilization model to promote health literacy among the 20 samples that used the model. Research instruments were questionnaires, assessment tools, and evaluation form. The research results showed that the technology utilization model to promote health literacy in the learning resource center for the elderly consisted of seven components: the target group, objectives, management, place, contents, technological education media, and assessment tools, which comprised three procedures consisting of: the preparation and planning for learning, activities organization, and evaluation. Seven experts assessed the model at the high suitability level (x = 4.46). The results revealed higher average scores on the posttest than on the pre-tests among the elderly who used the technology utilization model at the level of significance of .05. The result of evaluating the success of learning activity by using the model was 70 percent.